2013
DOI: 10.1021/bi400077b
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Interaction of Crataeva tapia Bark Protein with Heparin and Other Glycosaminoglycans

Abstract: CrataBL, a protein isolated from Crataeva tapia bark, which is both a serine protease inhibitor and a lectin, has been previously shown to exhibit a number of interesting biological properties, including anti-inflammatory, analgesic, anti-tumor, and insecticidal activities. Using a glycan array we have now shown that only sulfated carbohydrates are effectively bound by CrataBL. Since this protein was recently shown to delay clot formation by impairing the intrinsic pathway of coagulation cascade, we considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
14
0
4
Order By: Relevance
“…CrataBL activates caspase-3 in DU145 and PC3 cells ( Figure 11 ), similarly to what Jow et al [63] found on leukemia cells treated with beauvericin, a cyclic hexadepsipeptide. Zhang et al [64] showed that CrataBL strongly binds a number of sulfated carbohydrates whereas binding of other carbohydrates is insignificant, concluding that charge-charge interactions are responsible for lectin properties of this protein. In Figure 12 we show the positively charged surface regions in CrataBL, confirming their basic character.…”
Section: Resultsmentioning
confidence: 99%
“…CrataBL activates caspase-3 in DU145 and PC3 cells ( Figure 11 ), similarly to what Jow et al [63] found on leukemia cells treated with beauvericin, a cyclic hexadepsipeptide. Zhang et al [64] showed that CrataBL strongly binds a number of sulfated carbohydrates whereas binding of other carbohydrates is insignificant, concluding that charge-charge interactions are responsible for lectin properties of this protein. In Figure 12 we show the positively charged surface regions in CrataBL, confirming their basic character.…”
Section: Resultsmentioning
confidence: 99%
“…However, the 2-N-sulfo group of the middle pyranose ring and the 6-O-sulfo group of the fifth ring are both in proximity to the arginines previously implicated in binding, Arg 587 and Arg 590 , respectively 4, 8, 10, 39. SPR using heparinoid libraries and glycan array binding studies have both indicated that sulfate groups at 2-N and 6-O are more critical than at 2-O 19, 44. The four modeled fondaparinux sulfates, close to these arginines, superimpose within 2–4 Å of sulfates that were resolved in the SOS complex 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant activity of the heparin highly relies on its specific structure sequence, within which the binding site of an important protein (antithrombin III) is crucial for heparin to prevent the generation of a fibrin clot which is formed by the action of thrombin (SchedinWeiss, Richard, Hjelm, & Olson, 2008). Understanding of this structure-activity relationship of heparin offers the opportunity to develop drugs with higher specificity and better regulation of coagulation and to explore other therapeutic applications such as infection, inflammation, cancer and wound-healing treatment (Linhardt, 2003;Rajangam et al, 2006;Sakiyama-Elbert, 2014;Zhang et al, 2013a;Zhang, Wardwell, & Bader, 2013b). CS/DS chains are composed variably sulfated N-acetylgalactosamine and glucuronic acid or its epimeride iduronic acid disaccharides repeating units (Silbert & Sugumaran, 2002;Takegawa et al, 2011).…”
Section: Bioactive Polysaccharides From Other Sourcesmentioning
confidence: 99%